The Climate is Changing and So Must We: The Need to Prioritize At-Risk Communities and Ecosystems - Jaclyn Lopez (Washington University Journal of Law and Policy, 2024)
The climate is changing, and our laws and policies threaten to leave behind vulnerable communities and ecosystems. About half of the people and imperiled plants and animals in the United States are in coastal counties. Coastal communities’ ability to cope with the impacts of climate change will depend on how well local adaptation and resiliency laws and policies work to protect them from rising seas, flooding, saltwater intrusion, intensifying storm activity, and increased heat indices. At the same time, these very same adaptation laws and policies may inadvertently harm vulnerable communities and biodiversity. By 2040 – when today’s kindergarteners graduate college – Florida’s population will increase by 20% and sea levels will rise an additional foot. With its low elevation and location at the end of Hurricane Alley, Florida is “ground zero” for climate change impacts in the United States. The region’s struggles with industrial pollution create additional risk factors. Marginalized communities and imperiled biodiversity are caught amid climate impacts and existing, dangerous infrastructure. Florida is an apt case study for exploring concepts such as managed retreat, social vulnerability, species extinctions, assisted migration, and adaptive management. This Article concludes by making general recommendations for local governments looking to proactively center their resiliency and adaptation efforts on the survival of vulnerable communities and imperiled plants and animals.
Keywords: FloridaClimateCrisis; BiodiversityProtection; VulnerableCommunities; ResiliencyPlanning; ClimateAdaptation